The collision of masses and the way prices react to expectations - Chávez Guzmán, Luis (Elsevier Science, 2004)
When a body is impacted by other bodies its position is determined by the force of the impacts, likewise the price of a share is determined by expectations. This study intents to establish taxonomy of expectations based on the different types of impacts a body can receive, these can be: a blow without penetration, a blow that penetrates and stays in the body, a blow that goes through the body without affecting the body mass, and lastly, a blow that reduces but does not penetrate the body mass.